Essays of Trade Union History of the First Economic (Commercial) Education Institution in Russia - P. Kh. Katabay; V. I. Resin; M. I. Skripnikova; Yu. I. Smirnov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article shows the process of founding and developing trade union functions at education institutions. On the ground of factual material the role and importance of the Russian Plekhanov University of Economics were studied in different periods of interaction between workers of people’s education and society and state in order to ensure their defense in sphere of labour. Today the Professional Union of Workers of People’s Education and Science of the Russian Federation keeps upholding social and labour rights and professional interests of teachers, pre-school nurses, lecturers and other workers of education. The principle goal of developing contractual regulation in social and labour relations is to improve its quality and efficiency for workers of education. The trade union has joined both Russian and international union movement. When we reveal history of the trade union, it can help union bodies and activists comprehend both the past and the present significance of the trade union movement in education.